Generating Political Commitment for Regulatory Interventions Targeting Dietary Harms and Poor Nutrition: A Case Study on Sugar-Sweetened Beverage Taxation in Australia - Tristan Dry; Phillip Baker (Kerman University of Medical Sciences, 2022)
Background  Sugar-sweetened beverage (SSB) taxes are an effective public health policy intervention for improving nutrition and public health. Although implemented in over 50 jurisdictions worldwide, this intervention remains vastly underutilised, and in Australia political commitment for such a tax is low. The aim of this study is to understand the politics of SSB taxation in Australia, what factors have constrained political commitment for a tax, and what might enable such commitment in future.Methods  We adopted a case study design, guided by a theoretical framework developed from the political economy of nutrition literature. Data were collected from 16 interviews with informants from multiple sectors, supported by media articles, journal articles, and grey literature. Data were coded and organized by thematic analysis, and synthesised into the final results.Results  Nutrition actors have made significant progress in generating commitment for a SSB tax by producing relevant evidence, raising awareness, advocating for action, employing resonating frames, collaborating with civil society organisations, and forming coalitions increasing their overall cohesion. Nevertheless, political commitment for a SSB tax is low and was found to be impeded by the powerful influence of the food, beverage, and sugar industries, opposition from both major Australian political parties, ideological resistance to regulation, a low quality monitoring and surveillance system for food and nutrition, and limited public advocacy. The influence of nutrition actors was also impeded by weak connections to key policy-makers and missed collaborative opportunities with pro-SSB tax organisations.Conclusion  The identification of several impediments provides an explanation for why political commitment for a SSB tax is low in Australia and reveals several opportunities for how it might be generated in the future. Political commitment may come about through, for example, actions to limit the influence of industry in policy decision-making, and by strengthening the existing pro-SSB tax coalition.